2002
DOI: 10.1007/s11661-002-0262-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and electrical properties of Nb2AlC, (Ti, Nb)2AlC and Ti2AlC

Abstract: The heat capacities, thermal-expansion coefficients, thermal and electrical conductivities of Nb 2 AlC (actual Nb:Al:C mole fractions: 0.525 Ϯ 0.005, 0.240 Ϯ 0.002, and 0.235 Ϯ 0.005, respectively), Ti 2 AlC and (Ti, Nb) 2 AlC (actual Ti:Nb:Al:C mole fractions: 0.244 Ϯ 0.005, 0.273 Ϯ 0.005, 0.240 Ϯ 0.003, and 0.244 Ϯ 0.005, respectively) were measured as a function of temperature. These ternaries are good electrical conductors, with a resistivity that increases linearly with increasing temperatures. The resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
101
4
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 22 publications
14
101
4
2
Order By: Relevance
“…As reported previously, the volume thermal expansion coefficient of Ti 2 SC and Ti 2 AlC is experimentally measured to be 2:52 Â 10 À5 K À1 and 2:61 Â 10 À5 K À1 respectively, larger than the present calculation. 19,20) It is known that additional expansion can be caused by lattice vacancies. 21) It has been found that carbon vacancies in VC significantly increase the thermal expansion coefficient.…”
Section: Computational Detailsmentioning
confidence: 99%
“…As reported previously, the volume thermal expansion coefficient of Ti 2 SC and Ti 2 AlC is experimentally measured to be 2:52 Â 10 À5 K À1 and 2:61 Â 10 À5 K À1 respectively, larger than the present calculation. 19,20) It is known that additional expansion can be caused by lattice vacancies. 21) It has been found that carbon vacancies in VC significantly increase the thermal expansion coefficient.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Alloying on M and A sites has been extensively studied, and a large number of MAX phases synthesized, with resultant change in, e.g., elastic properties and hardness of Ti 3 (Si,Al)C 2 [4] and (Ti.V) 2 AlC [5], respectively, or conductivity in (Ti,Nb) 2 AlC [6]. Partial replacement of one element by another can also increase the stability, observed for (Cr,V) 3 AlC 2 [7].…”
Section: Introductionmentioning
confidence: 97%
“…[2] Partial substitution of the M, A, or X elements is a process by which the MAX phase properties can be tailored. For example, the elastic modulus of Ti 3 (Si,Al)C 2 , [3] hardness of (Ti,V) 2 AlC, [4] and conductivity of (Ti,Nb) 2 AlC [5] can be tuned in between the values of the end members. To date, most of the substitutions have been with elements chosen from those used in previously synthesized MAX phases.…”
Section: Introductionmentioning
confidence: 99%